Indicative Scorekeeping - Willer, Malte (Proceedings of the Amsterdam Colloquium, 2013)
Folklore has it that counterfactual Sobel sequences favor a variably strict analysis of conditionals over its plainly strict alternative. Recent discussions of the lore have focussed on the question whether data about reverse counterfactual Sobel sequences actually speak in favor of a dynamic revival of the strict analysis. This paper takes the discussion into a new direction by looking at straight indicative Sobel sequences. The observation is that a variably strict analysis fails to predict the felicity of these sequences given minimal semantic and pragmatic assumptions. A properly elaborated dynamic analysis of indicatives, in contrast, handles the data with grace.